pengaruh Ukuran Perusahaan dan Struktur Modal Terhadap nilai Perusahaan pada Sektor Property & Real Estate Yang terdaftar di Bursa Efek Indonesia Tahun 2019 - 2023 - Lestari, Novi; Rahayu, Dhea Nova (Lentera Ilmu Madani, 2025)
The objectives to be achieved in this study are: (1) To determine the effect of company size on the value of Property & Real Estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. (2) To determine the effect of capital structure on the value of Property & Real Estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. (3) To determine the effect of company size and capital structure on the value of Property & Real Estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. The data used in this study are data based on annual financial reports obtained through the official website of the Indonesia Stock Exchange www.idx.com. Sampling using a purposive sampling method and selected 31 manufacturing companies in the property & real estate subsector in 2019-2023 as samples in the study. Based on the results of the study using multiple linear regression analysis. The results of the F Test study show that company size and capital structure simultaneously affect company value with a significance value of 0.032. The t-test results show a significance value of 0.247 for company size and 0.026 for capital structure. This means that company size has no effect, and capital structure does affect company value.